2017
DOI: 10.1596/978-1-4648-0518-9
|View full text |Cite
|
Sign up to set email alerts
|

Disease Control Priorities, Third Edition (Volume 5): Cardiovascular, Respiratory, and Related Disorders

Abstract: This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of The World Bank concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 567 publications
(770 reference statements)
0
20
0
Order By: Relevance
“…To the best of our knowledge, there have been no previous costing studies on RHD in Africa and, only one prior costing study in a low-and middle-income country setting. Terreri et al, looking at RHD in Brazil, quanti ed per-patient direct costs of RHD and rheumatic fever from the provider perspective using the ingredients approach [1]. Even after adjusting to a common currency and year, the cost estimates in this study are higher than in the Brazilian study, probably due to advances in care (i.e.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…To the best of our knowledge, there have been no previous costing studies on RHD in Africa and, only one prior costing study in a low-and middle-income country setting. Terreri et al, looking at RHD in Brazil, quanti ed per-patient direct costs of RHD and rheumatic fever from the provider perspective using the ingredients approach [1]. Even after adjusting to a common currency and year, the cost estimates in this study are higher than in the Brazilian study, probably due to advances in care (i.e.…”
Section: Discussionmentioning
confidence: 57%
“…Rheumatic heart disease (RHD) is the most common acquired cardiovascular disease among children and adolescents in low-and middle-income countries [1,2]. It is a chronic in ammatory disease of the heart valves that result from recurrent episodes of acute rheumatic fever (ARF).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Controlling blood pressure (BP) through daily, low-cost, medications substantially reduces the negative consequences of hypertension and is one of the most cost-effective ways of reducing mortality. 2–4 BP control is especially pressing in urban India, since over 30% of adults over the age of 30 are hypertensive and this prevalence is expected to increase substantially as the population ages. 5–7 Indeed, recent observational studies have found that improving BP control has the potential to result in large population-wide improvements in mortality in urban India and similar contexts.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Behavioral risk factors for NCDs, especially suboptimal diet, are prevalent as lifestyle changes because of the rapid economic growth in China. 1,8 As the dietary pattern among the Chinese has been dramatically westernized in the past two decades, the consumption of sugar-sweetened beverages (SSBs) increased steadily. [9][10][11][12] According to a national cross-sectional survey among 1584 adults aged 18 to 55 years in urban China in 2016, about half of them consumed more than one serving of SSBs per day.…”
Section: Introductionmentioning
confidence: 99%